Boundary value problem with integral conditions for a linear third-order equation - M. Denche; A. Memou (Journal of Applied Mathematics)
We prove the existence and uniqueness of a strong solution for a linear third-order equation with integral boundary conditions. The proof uses energy inequalities and the density of the range of the generated operator.